Pelatihan Literasi Keuangan Melalui Pengaplikasian Akuntansi Bagi Siswa di SMK Karmel Kota Tangerang - Andy Andy; Selfiyan Selfiyan; Agus Kusnawan; Dian Anggraeni; Peng Wi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Financial literacy training based on Financial Management through Accounting at SMK Karmel is an important aspect in preparing students to face the challenges of the business world in the digital era. Based on qualitative research through observation, interviews, and documentation studies, this training has proven to have a positive impact on improving students' financial literacy knowledge and skills. They gain an understanding of the concept of Financial Management through Accounting, online marketing strategies, financial management, and product innovation. In addition, this training teaches the use of digital platforms to market products, build brand awareness, and measure the effectiveness of marketing campaigns. On the other hand, this training also succeeded in developing proactive, creative, innovative, and adaptive attitudes that are needed in the dynamic modern business world. Students are equipped with the ability to innovate to create products or services that are relevant to market needs and are ready to adapt to technological changes that continue to develop. One of the other positive impacts is the increase in students' confidence in starting their own businesses, so that they not only rely on formal jobs, but also begin to consider financial literacy as a career path. To increase the effectiveness of this program, it is recommended that the scope of the training be expanded to include topics such as e-commerce and data analysis, as well as strengthen cooperation with financial management actors through Accounting. In addition, the integration of training into the vocational curriculum will ensure the sustainability of the program and provide opportunities for all students to gain the necessary financial literacy skills. Thus, this training is expected to prepare students of SMK Karmel to be more competitive and ready to face the modern business world that continues to grow.